Membrane transporters and carbon metabolism implicated in chloride homeostasis differentiate salt stress responses in tolerant and sensitive Citrus rootstocks - Brumos, Javier; Colmenero-Flores, José M.; Conesa, Ana; Izquierdo, Pedro; Sanchez, Guadalupe; Iglesias, Domingo J.; Lopez-Climent, Maria F.; Gómez-Cadenas, Aurelio; Talón, Manuel (2017)
Salinity tolerance in Citrus is strongly related to leaf chloride accumulation. Both chloride homeostasis and specific genetic responses to Cl(-) toxicity are issues scarcely investigated in plants. To discriminate the transcriptomic network related to Cl(-) toxicity and salinity tolerance, we have used two Cl(-) salt treatments (NaCl and KCl) to perform a comparative microarray approach on two Citrus genotypes, the salt-sensitive Carrizo citrange, a poor Cl(-) excluder, and the tolerant Cleopatra mandarin, an efficient Cl(-) excluder. The data indicated that Cl(-) toxicity, rather than Na(+) toxicity and/or the concomitant osmotic perturbation, is the primary factor involved in the molecular responses of citrus plant leaves to salinity. A number of uncharacterized membrane transporter genes, like NRT1-2, were differentially regulated in the tolerant and the sensitive genotypes, suggesting its potential implication in Cl(-) homeostasis. Analyses of enriched functional categories showed that the tolerant rootstock induced wider stress responses in gene expression while repressing central metabolic processes such as photosynthesis and carbon utilization. These features were in agreement with phenotypic changes in the patterns of photosynthesis, transpiration, and stomatal conductance and support the concept that regulation of transpiration and its associated metabolic adjustments configure an adaptive response to salinity that reduces Cl(-) accumulation in the tolerant genotype.